Interactive E-book in Problem-Based History Learning to Enhance Students' Knowledge of the Fall of the Dutch East Indies - Haidar Trisna Tanaya (Indonesian Journal of History Education, 2024)
History is often perceived as monotonous and unengaging by students, primarily due to traditional teaching methods focused on memorization with minimal interaction. This issue is exacerbated by the lack of innovative learning media aligned with technological advancements. This study aims to develop an interactive e-book as a history learning tool, integrating real-world problems, specifically "The Fall of the Dutch East Indies," for Grade XI students at SMA NU 05 Brangsong (Private High School). The interactive e-book is expected to increase the appeal of history lessons, foster more active interaction, and help students gain a deeper and more comprehensive understanding of the subject through engaging and easily understandable visualizations. The study employs the Research and Development (R&D) method with a modified 4D development model, reducing it to 3D: Define, Design, and Develop. Data was collected through observation, interviews, document studies, and surveys. Qualitative and quantitative data analyses were used to evaluate the effectiveness and feasibility of the developed learning media. The results demonstrate that the interactive e-book is viable for use and effectively enhances students' understanding of historical topics, particularly the fall of the Dutch East Indies. This research underscores the importance of integrating technology in history education to improve student engagement and learning outcomes.